Building a sustainable creative economy: The influence of capital access and government programs - Wijoyo, Handoko Sosro Hadi; Mujanah, Siti; Susanti, Nanis (Edelweiss Applied Science and Technology, 2024)
The future of Indonesia’s economy lies in the creative economy, contributing to GDP and creating jobs. This research is important to understand the policies, entrepreneurial skills, and impact of the creative industry on cultural heritage. The creative industry in Bojonegoro faces the challenge of limited research in several areas. This study analyzes the relationship between access to capital, cultural heritage, and government programs on the performance and growth of the creative industry. This study uses a quantitative method with SEM-PLS to analyze the complex relationships between constructs in the creative industry in Bojonegoro. Samples were taken purposively from creative industry players, with 127 respondents. Data were collected through questionnaires, interviews, and observations to understand the factors that influence the growth of the creative industry. The variables studied include Government Programs, Cultural Heritage, Access to Capital, Creative Industry Performance, and Creative Industry Growth. Testing is done by ensuring the validity and reliability of the data, and analyzing R-Square and hypotheses using T-statistics to confirm the relationship between variables. In this analysis, the accepted hypothesis shows that access to capital has a significant effect on access to capital with an O value of 0.850, T-statistics 23.307, and P-values 0.000. In addition, access to capital also has a positive effect on the growth of the creative industry with O 0.494, T-statistics 5.213, and P-values 0.000. The performance of the creative industry also has a significant effect on the growth of the creative industry, with O 0.446, T-statistics 4.129, and P-values 0.000. Finally, access to capital through the performance of the creative industry has a positive effect on the growth of the creative industry, with O 0.379, T-statistics 4.117, and P-values 0.000. This study confirms the importance of access to capital in supporting the performance and growth of the creative industry. This study found a significant relationship between access to capital, creative industry performance, and the growth of the creative industry in Indonesia. The hypothesis stating that access to capital has a positive effect is accepted, while the hypothesis related to cultural heritage and government programs is rejected. Policy recommendations are focused on strengthening access to capital and preserving cultural heritage to support sustainable creative industries.